Asesmen potensi geopark untuk pengembangan geotourism berbasis edukasi pada Goa Lowo Trenggalek - Robby Hilmi Rachmadian; Tasya Khairunisa; Purwanto Purwanto (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2023)
The Goa Lowo Tourism Object, Trenggalek Regency, East Java is one of the geosites with its own charm in the form of karst rock morphology which produces a spectacular karst cave display case. Improving the quality of tourism objects with the potential for education-based geotourism is one way to develop natural potential that has yet to be maximized. This study aims to conduct a geodiversity study on geological elements, examine the value of science, education, tourism, to the risk of degradation in the Goa Lowo area, and a geotourism development strategy based on Research Area Education. This research is expected to be the basis for developing geoparks in the Goa Lowo area. The research method used includes an assessment of the potential of geological sites, measured through several criteria, parameters, and indicators quantitatively, with the reference standard used to conduct this assessment based on a quantitative assessment conducted by the Center for the Geological Survey. The criteria used in this assessment are the parameters of science value, education value, tourism value, and degradation risk value with a predetermined weight. Based on the results of the assessment carried out, the weight value of science is 65 percent, education is 72.5 percent, tourism is 87.5 percent, and the risk of degradation is 58.75 percent. Based on the final results of the quantitative assessment, the total value of the assessment on the Goa Lowo geosite is 283.75 percent, which is between 201-300 which can be interpreted as having a medium category. Kawasan Objek Wisata Goa Lowo Kabupaten Trenggalek Jawa Timur merupakan salah satu geosite dengan daya tarik tersendiri berupa morfologi batuan karst yang menghasilkan etalase goa karst yang spektakuler. Meningkatkan kualitas objek pariwisata dengan potensi geotourism berbasis edukasi adalah salah satu cara mengembangkan potensi alam yang belum maksimal. Penelitian ini bertujuan untuk melakukan kajian geodiversity pada unsur geologi, mengkaji nilai ilmu pengetahuan, pendidikan, pariwisata, hingga risiko degradasi di kawasan Goa Lowo, dan strategi pengembangan geotourism berbasis Edukasi Daerah Penelitian. Penelitian ini diharapkan dapat menjadi dasar pengembangan geopark di kawasan Goa Lowo. Metode penelitian yang digunakan meliputi asesmen potensi situs geologi, diukur melalui beberapa kriteria, parameter, serta indikator secara kuantitatif, dengan standar acuan yang digunakan untuk melakukan asesmen ini adalah berdasarkan penilaian kuantitatif yang dilakukan oleh Pusat Survei Geologi. Kriteria yang digunakan dalam asesmen ini adalah parameter nilai sains, nilai pendidikan, nilai pariwisata, dan nilai risiko degradasi dengan bobot yang telah ditetapkan. Berdasarkan hasil asesmen yang dilakukan, bobot nilai sains 65 persen, pendidikan 72,5 persen, pariwisata 87,5 persen, dan risiko degradasi 58,75 persen. Berdasarkan pada hasil akhir asesmen kuantitatif, maka didapatkan total nilai asesmen pada geosite Goa Lowo sebesar 283,75 persen yaitu antara 201-300 yang dapat diartikan memiliki kategori sedang.